Could chronotype be a risk factor for unhealthy eating and prediabetes? - Celen, Mecde; Ince, Nezire (Taylor & Francis Ltd, 2024)
ObjectiveTo examine the possible effects of chronotype on nutritional status and fasting blood glucose(FBG) among female university students. Method: The study was conducted in two stages.In the first stage,the chronotype of the participants were determined by applying the Morningness Eveningness Questionnaire(MEQ) questionnaire to 384 students.Also physical activity records and sociodemographic characteristics were questioned. Women who didn't meet the criteria were eliminated.In the second stage, study groups were formed with 92 students(46 evening and 46 morning type). Afterwards,3-day food consumption records were taken from 92 participants and FBG measurements were taken only from the volunteers. Results: Significant differences were found between the food consumption and FBG values of students of different chronotypes. Evening type students' protein(g),protein percentage, fiber intake were found to be significantly low, while carbohydrate percentage intakes were higher(p < 0.05).Also BMI(beta = -0.240; p < 0.05) and FBG(beta = -0.314; p < 0.05) were found significant predictors of MEQ scores whereas age was not(beta = -0.136; p > 0.05). Conclusions: Dieticians/nutritionists should give nutritional advice to the students and organize their diet by considering their chronotype to prevent health problems that may arise.
Keywords: Chronotype; nutritional status; fasting blood glucose; university students